Governance disclosure quality and market valuation of firms in UK and Germany. (6th October 2020) - Ullah, Subhan; Ahmad, Sardar; Akbar, Saeed; Kodwani, Devendra; Frecknall‐Hughes, Jane
Abstract: This study develops a "comply or explain" index which captures compliance and quality of explanations given for non‐compliance with the corporate governance codes in UK and Germany. In particular, we explain, how compliance and quality of explanations provided in non‐compliance disclosures, and various other internal corporate governance mechanisms, affect the market valuation of firms in the two countries. A dynamic generalised method of moments (GMM) estimator is employed as the research technique for our analysis, which enabled us to control for the potential effects of endogeneity in our models. The findings of our content analysis suggest that firms exhibit significant differences in compliance, board independence and ownership structure in both countries. The "comply or explain" index is positively associated with the market valuation of UK firms suggesting that compliance and quality governance disclosure are value relevant in the UK. Institutional blockholders' ownership is, however, negatively associated with the market value of firms, which raises questions about the monitoring role of institutional shareholders in both countries. We argue that both compliance and explanations given for non‐compliance are equally important, as long as valid reasons and justifications for non‐compliance are provided by the reporting companies. These findings thus imply that the "comply or explain" principle is working well and that UK and German companies could benefit from the flexibility offered by this principle. With respect to the role of board size, board independence, ownership structure, and institutional ownership of firms, this study offers policy implications.